Estudo silvicultural e da viabilidade econômica do manejo da vegetação do cerrado - Mello, Anabel Aparecida de (1999)
This study was performed aiming to compare different levels of intervention (remotion 50, 70, 80, 90 and 100% of the basal area and the control) in the vegetation of the savana “stricto sensu”. The data for accomplishment of this study were obtained in the Alvação farm, municipal district of Coração de Jesus, north of the state of Minas Gerais. Evaluations were accomplished in the years of 1986, 1996 and 1998 in 30 plots of 600m2 installed in an area of 30 ha subjected to 6 treatments. These consisted in: remotion of 50%, 70%, 80%, 90% and 100% of the basal area, besides the control, with 5 repetitions each. In these it was obtained the number of trees and the basal area of the plants with circumference at 1,30m of height (CAP) larger or equal to 15,7 cm. Chapter 1 deals with the objective of statisticaly comparing the development of the number of trees and the basal area after 10 years of apllying intervention levels. Using a covariance analysis the results alowed to conclude that the experiment was still in the growing stage at the time of its installation. In areas where 100% of the basal area had been removed presented the largest growth rate in number of trees and basal area, it could suggest a 12 years cutting cycle, considering the number of trees and a 10 years cutting cycle considering the basal area. The objective of chapter 2 was to verify the impact caused in the structure and diversity of remaining vegetation after 10 years of application of different levels of intervention, using indices that represented the vegetation structure. It was observed that the Leguminosae family presented the largest number of species and the Vochysiaceae family presented the largest number of individuals. After 10 years of intervention the remaining vegetation presented indices of diversity similar to other areas wich did not suffer intervention, showing that there was no significant lost in diversity. For the chapter 3 it was used data from inventories carried out on 1996 and 1998 to estimate the forest production until the year 2007. To perform this prognosis the transition matrix was used. The found results where: the prognosis showed that all levels of intervention were superior in at least 50% of the number of measured plants in 1986 and the growth rate of remaining vagetation was superior to those that did not suffer any intervention showing that it is viable to intevene in the savana vegetation. The objective of chapter 4 was to verify the economic viability of interventions and to compare management options for the savana with the option of reforestation with eucalyptus. Through the use of Net Present Value (VPL) method with infinite horizon it was conclud that the exploitation of the savana for production of fire wood is economicaly viable considering the price levels of wood, production costs and condictions of production for all management regimes mentioned in this study with the exception of the remotion of 50% of the basal area. The best economic option for all treatments proved to be a 10 years cutting cycle with the remotion of 90% of the basal area showing the best economic return. Fron the economic stand point of view, to invest in eucalyptus plantations in areas of savana aiming to produce wood for energy is of more interest over the management of the savana vegetation only if the productivity of the eucalyptus is over 45st/ha/year.